2014
DOI: 10.4103/0974-2077.146664
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant narrow band UVB improves the efficacy of oral azithromycin for the treatment of moderate to severe inflammatory facial acne vulgaris

Abstract: Background:Acne vulgaris (AV) is a common inflammatory disease of the pilosebaceous unit. A variety of treatment modalities are available for the treatment of AV. Among the available options, oral azithromycin is popularly prescribed for its proven anti-inflammatory effects. Narrow band UVB (NBUVB) also has a potent anti-inflammatory action. Concomitant use of both modalities may result in a synergistic therapeutic response; however, the combined efficacy has not yet been evaluated for the treatment of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Alternative acne treatments include blue light, ultraviolet (UV) phototherapy, and photodynamic therapy [117,118,119]. These approaches could improve acne by reshaping the skin microbiota and lowering C. acnes counts within the lesions.…”
Section: Acne Treatment and Skin Microbesmentioning
confidence: 99%
“…Alternative acne treatments include blue light, ultraviolet (UV) phototherapy, and photodynamic therapy [117,118,119]. These approaches could improve acne by reshaping the skin microbiota and lowering C. acnes counts within the lesions.…”
Section: Acne Treatment and Skin Microbesmentioning
confidence: 99%
“…In fact, UV's impact on acne had been widely a few studies. [18][19][20] However, more studies reached a same conclusion that this beneficial effect was slight and not sufficient for therapeutic use considering side-effect of its long-term use such as carcinogenesis and photoaging. 21,22 As a result, UV-based therapy was thought obsolete in the treatment of acne vulgaris.…”
Section: Overall and Interactive Effects Of Low Levels Of Uv Exposurementioning
confidence: 99%
“…A case report by Zeichner et al showed improvement in inflammatory papules and pustules in a pregnant patient after two months of NB-UVB therapy [ 55 ]. A recent study of 104 patients demonstrated that oral azithromycin in combination with NB-UVB led to improvement of inflammatory papules when compared to oral azithromycin alone [ 56 ].…”
Section: Reviewmentioning
confidence: 99%